Search for New Bioactive Marine Natural Products and Application to Drug Development - Kobayashi, Jun’ichi (Chemical & pharmaceutical bulletin, 2016)
Natural products are well recognized as an important source of lead compounds in drug development. During the past >30 years, we have discovered >1000 novel bioactive natural products from Okinawan marine organisms (sponges, tunicates, cone shells, etc.) and microorganisms (fungi, bacteria, dinoflagellates, etc.). Some of them are used as bioprobes useful for basic studies of life sciences, while others are expected to be candidates of drug leads.